An efficient star-shaped fused-ring electron acceptor with C3h-symmetric core via thieno[3, 2-b]thiophene extending conjugation strategy. (30th September 2020) - Wang, Weijie; Wang, Tong; Wu, Xiaofu; Tong, Hui; Wang, Lixiang
Abstract : A star-shaped fused-ring electron acceptor, BTTCTT-ICF, with thieno[3, 2- b ]thiophene extending conjugation exhibits a narrow optical bandgap of 1.54 eV and PCE of 10.39% on blending with the polymer donor PM6 . Abstract : The thieno[3, 2- b ]thiophene (TT) unit is a classic building block to construct high-performance fused-ring electron acceptors (FREAs) for organic solar cells (OSCs). In this work, a star-shaped FREA BTTCTT-ICF based on a new C 3h -symmetric fused-ring core BTTCTT was designed and synthesized by introducing the TT unit to extend the π-conjugation. Due to its strong electron-donating ability and efficient π-electron delocalization, BTTCTT-ICF exhibited a narrow optical bandgap of 1.54 eV and a high absorption extinction coefficient of 3.6 × 10 5 M −1 cm −1 . The blend film of BTTCTT-ICF and the wide bandgap polymer PM6 produced a complementary absorption and a broad EQE spectral range covering 300 to 850 nm. When treated via thermal annealing, the PM6 :BTTCTT-ICF blend film exhibited more ordered molecular packing and a suitable phase morphology, which improved its charge mobility and device efficiency. Consequently, the PM6 :BTTCTT-ICF -based inverted device achieved the best power conversion efficiency (PCE) of 10.39% with a high short-circuit current density ( J sc ) of 16.77 mA cm −2, open-circuit voltage ( V oc ) of 0.91 V and fill factor (FF) of 68.08%. Our results demonstrate that the extension of the star-shaped fused-ring core by TT units is a rational and effective strategy for achieving highly efficient star-shaped FREAs.